Anthropometric parameters and field test results of young athletes on follow-up study - Petridis, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purpose of this study was to examine the effect that, body height and body weight changes can have on physical tests performance in pre-pubertal and pubertal athletes. Improvement of conditioning abilities at that age can vary according to the athletes` age period, their sport and their gender. Methods: A total of 79 athletes were measured (40 boys and 39 girls) practicing in either basketball or handball. The subjects were divided into two age groups (n = 42 of 11-12years old and n = 37 of 13-14 years old). Data were obtained in two separate measurements, in spring of 2010 and in autumn of 2011, thus the changes of data were recorded within a 16 month period. Body height (BH), body weight (BW), vertical jump (VJ), 30 m sprint run and 2800 m run were measured at the two time periods. Regression analysis was used to analyze the effect of the body parameters and grouping factor on the physical tests performance. Results: BH changed 4.6±2.44%, BW 13.0±9.95%, 30m 6.12±11.72%, VJ 16.93±23.37% and 2800m 5.93±11.04%. In both age groups (11-12 & 13-14 years) boys basketball players had a faster growth in BH and in BW, however in all three physical tests had lower improvement compared to handball players. Among body parameters BH had a significant effect on the 30m run (â = 0.39; t = 2.78; p < 0.05), while the BW, sex, age group and sport didn`t show to effect 30m run performance. On vertical jump BH showed significant effect (â = 0.42; t = 3.23; p < 0.05), BW had a negative, but not significant effect. Between boys and girls, there was a slight, but not significant difference, with boys performing higher. 2800m run, didn`t seem to be effected by any parameter. Discussion: It seems that among the three physical tests, at the pre-pubertal age BH can be important only in 30m run, which has a logical explanation, while there is no difference in the improvement pace between boys and girls, as also between basketball and handball players. In many aspects a similarity between the two sports conditional requirements and between the training patterns can explain the lack of any improvement alterations in this age group.